The Influence of Mining Sand Toward Income and Livelihoods of Fishermen In Petapahan Village Tapung Subsdistrict Kampar District Riau Province - Dewi Indatul Fitri; Darwis '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in February 2017 which located in Petapahan Village Tapung Subsdistrict Kampar District Riau Privince. This study was aimed to knowledge the changing income from fish catch before and after the introduction of sand mining and analyze the influence of factors age, education and asset ownership on changes in livelihoods fishermen. Methods used in this research is a method of survey with 50 respondents determinatied by the census. There is a decrease in revenue from fishing with average IDR 2.154.000,- per month (68 %) after activity the introduction of mining sand, namely from IDR 3.268.667,- per month to IDR 1.114.667,- per month and significant statistically Factors that effecting a change of livelihoods fishermen significantly are age of fishermen and asset ownership, but the education level not significant .Keywords: income, livelihood, sand mining, Tapung River